Problematics of Unrequited Love in the Modern Javanese Song â€œKlebusâ€ by Ngatmombilung (Critical Discourse Analysis) - Eryneta Nurul Hasanah; S. Nudia Mastur (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2023)
Love can be interpreted as a process that occurs in society, begins with a feeling of happiness, romance, and harmony. However, love can also end in heartbreak, disappointment, unrequited love, suffering, and so on. One of the sad endings to love experinced by many people, especially young people, is unrequited love. This study aim to analyze the problematic nature of unrequited love in the modern Javanese song titled â€œKlebusâ€, which was popularized by Ngatmombilung. The research method is descriptive-qualitative with the critical discourse analysis approach of Norman Fairclough to explore the meaning of songs critically and in depth. Data collection techniques include document studies, content analysis, and interviews. Data analysis techniques are carried out in three dimensions, namely textual dimensions, discursive practice dimensions, and sociocultural practical dimensions, to get appropriate conclusions. This study shows that in the song